Wireless-powered cooperative energy aware anycast routing in wireless sensor networks. (November 2016) - Hadi, Fazle; Ahmed, Sheeraz; Minhas, Abid Ali; Al Mazyad, Abdulaziz; Islam, Najam ul; Ahmed, Imran; Javaid, Nadeem
A wireless-powered cooperative energy aware anycast routing protocol is proposed in this work. In contrary to conventional cooperative networks, it is considered here that all the relays did not have embedded energy supply, rather equipped with rechargeable batteries and energy harvesting units. Hence, from source signals, they accumulate sufficient harvested energy before the information is forwarded to its destination. Each relay between two basic modes will switch adaptively, which are information forwarding and energy harvesting. The research is limited to decode-and-forward scheme and fixed ratio combining, which works at the relay node of the network and the receiver end, respectively. The physical layer cooperative diversity and network layer multi-hop routing lead us to devise a minimum energy routing protocol as the joint optimization of power required for transmission at physical layer and also at network layer for the process to select a link. Simulating our algorithm demonstrates that the suggested cooperative energy aware anycast routing scheme has a better end-to-end delay and better ratio of packet delivery. Results further reveal that our proposed algorithm has improved energy consumption in comparison to the non-cooperative energy aware anycast scheme and the cooperation-based robust cooperative routing protocol scheme. Sensed data are allocated between nearby nodes by cooperative energy aware anycast routing in a cost-effective way in order to achieve maximum network lifetime.